2012
DOI: 10.1111/j.1365-2982.2011.01866.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in the irritable bowel syndrome: a review of the literature

Abstract: Patients with IBS appear to experience symptoms that may be the result of changes in ANS functioning. HRV measures in clinical routine may allow assessing these changes, but further studies performed in a standardized fashion should improve the validity of HRV measures for clinical research first.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
78
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 88 publications
(139 reference statements)
8
78
1
4
Order By: Relevance
“…24 IBS-C patients was focused on due to a unique pattern of HRV and GI symptoms. 5 IBS-C patients are known experience more severe upper GI symptoms and lower GI bloating than those with other subtypes of IBS, suggesting greater vagal mediation of afferent signals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 IBS-C patients was focused on due to a unique pattern of HRV and GI symptoms. 5 IBS-C patients are known experience more severe upper GI symptoms and lower GI bloating than those with other subtypes of IBS, suggesting greater vagal mediation of afferent signals.…”
Section: Introductionmentioning
confidence: 99%
“…Among the subtypes, IBS-C is the most prevalent, accounting for at least one-third to 58% of all IBS, particularly in females and younger individuals. [5][6][7][8][9] IBS interferes with social function, decreases quality of life, and increases health care costs. 10 A systematic review on IBS indicated that the direct annual cost of managing IBS ranges from approximately $1600 to $7500 per person.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, stress is able to modify visceral sensitivity as well as GI motility, permeability, intestinal microbiota, and immunity of the GI tract, all mechanisms that are involved in the pathophysiology of IBS. In addition, stress is able to modulate the hypothalamic pituitary adrenal (HPA) axis and the autonomic nervous system (ANS) which is the link between the gut and the CNS and an imbalance of the ANS is observed in IBS patients (Pellissier, et al 2010a;Mazurak, et al 2012). The main brain areas involved in stress are the prefrontal cortex, the limbic system (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the amygdala projects to the intermediolateral column cells of the spinal cord, at the origin of the sympathetic nerves, and locus coeruleus (LC) in the pons. It makes the amygdala able to modulate the sympathetic nervous system, the other branch of the ANS, and thus to modulate the sympatho-vagal balance, a marker of brain-gut interactions (Mazurak, et al 2012). iii) The amygdala controls the HPA axis activation either directly or indirectly via the hippocampus (i.e.…”
Section: Introductionmentioning
confidence: 99%